The Prognostic Value of PARP Expression in High-Grade Epithelial Ovarian Cancer - Molnár, Szabolcs (Pathol Oncol Res, 2020)
In an attempt to clarify the prognostic relevance of poly (ADP-ribose) polymerase (PARP) expression, we analysed the clinical data of 86 high-grade epithelial ovarian cancer (EOC) cases in which PARP immunohistochemistry results were available. Immunostaining to highlight PARP protein expression was performed using a Leica Bond MAX Immunostainer (Leica Microsystems, Wetzlar, Germany). We applied a rabbit polyclonal anti-PARP antibody (ab6079 330, Abcam, Cambridge, UK) for the specific reaction. The intensity and distribution of immunostaining were assessed by light microscopy (Leica DM2500 microscope, DFC 420 camera, and Leica Application Suite V3 software; Leica) and evaluated with a four-grade (0–3+) system. The median progression-free survival (PFS) was generated for each semiquantitative group of PARP expression among chemotherapy-naive cases at the time of PARP immunohistochemistry. Eighty-six cases were chemotherapy-naive at the time of PARP immunohistochemistry, and 41 cases showed no PARP expression. Forty-five cases showed intermediate or high PARP expression. The median PFS among patients in the PARP-negative group was 16 months (interquartile range; IQR 10.7–35.9 months), and the median PFS of patients in the PARP-positive group was 12 months (IQR 6.1–21.8 months). The difference was significant according to the log-rank test (p = 0.01). The median overall survival (OS) of patients in the PARP-negative group was 65 months (IQR 43.6–110.8 months), and the median OS of patients in the PARP-positive group was 52 months (IQR 36.9–66.7 months). The difference was significant according to the log-rank test (p = 0.028). Multiple comparisons confirmed that PARP expression results in a significant difference in PFS and OS achieved by first-line Taxol-carboplatin chemotherapy. The lack of PARP expression assessed by immunohistochemistry may predict improved PFS in ovarian cancer patients after adjuvant platinum-based chemotherapy.